Aplikasi Teknik Snowplow pada Restorasi Kelas IV Komposit Gigi dengan Fraktur Enamel-dentin: Laporan Kasus: Snowplow Technique Application in Direct Composite Restoration of a Class IV Enamel-dentin Fracture : Case Report - Rifa Khalisha Indrawan; Denny Nurdin (Fakultas Kedokteran Gigi IIK Bhakti Wiyata, Kediri., 2026)
Introduction: Restoration of a crown fracture in anterior teeth presents its own challenges due to the high risk of refracture caused by high masticatory load. This case report aims to describe the application of the snowplow technique in Class IV direct composite restoration of a tooth with an enamel-dentin fracture. Case: A 23-year-old female presented with a fractured right anterior tooth and a history of pain stimulated by drinking cold water and exposure to cold air. Tooth 11 was subjected to the enamel-dentin crown fracture and diagnosed with reversible pulpitis with Ellis Class II fracture. Management: Class IV direct composite restoration was performed using a combination of snowplow and incremental technique to obtain an optimal adaptation and reduce the risk of refracture. Conclusion: The snowplow technique possesses the superiority of producing excellent shear bond strength, minimizing the risk of refracture of the restoration. Moreover, the use of bulk-fill composite in the technique supports the aesthetic function of the anterior teeth restoration.